Theoretical approaches to the definition of the concept of energy security of the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
The article considers the main theoretical approaches to the definition of the concept of energy security, analyzes the work of domestic and foreign authors devoted to the study of the problems of ensuring energy security in the Republic of Kazakhstan and abroad. The author’s definition of energy security is proposed, as well as the relationship between national and energy security. Since energy has become one of the most important factors in ensuring economic growth and sustainable development of people, nations, societies and, ultimately, human civilization in the global scenario of the 21st century, there is an urgent need to consider energy as a strategic commodity and to analyze national, regional and global strategies in field of energy. Energy security and national security are closely interconnected, the threats first are likely to escalate as threats to the latter.Key words: security, national security, energy security, economic security, environmental safety, fuel and energy complex, energy resources, subsoil use.